The effectiveness of visual effects in short film among youth in Malaysia / Hazmeen Zainuddin - Zainuddin, Hazmeen (2013)
The purpose of this research is to study about the effectiveness of using visual effects in short film among youth in Malaysia. The problem of this research is to verify if can we we use visual effect for the short film that is low budget? And the second problem is it the short film with visual effect can also attract people same as big film with a big budget? Other than that, statistic of the number film viewers from the year of 2006 until February 2013 from Perbadanan Kemajuan Filem Nasional Malaysia (FINAS) have been state that can be seen about the interest of people in Malaysia in watching film in cinema. Also to support this study, the literature review established about the definition of short film and also the definition of visual effects.